Comparative effectiveness of six Chinese herb formulas for acute exacerbation of chronic obstructive pulmonary disease: protocol for systematic review and network meta-analysis. Issue 8 (11th August 2017) - Liu, Shaonan; Chen, Jing; He, Yihan; Wu, Lei; Lai, Jiaqi; Zuo, Jinhong; Yang, Lihong; Guo, Xinfeng
Abstract : Introduction: Chinese medicine is commonly used to combine with pharmacotherapy for the treatment of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Six Chinese herb formulas involving Weijing decoction, Maxingshigan decoction, Yuebijiabanxia decoction, Qingqihuatan decoction, Dingchuan decoction and Sangbaipi decoction are recommended in Chinese medicine clinical guideline or textbook, to relieve patients with phlegm-heat according to Chinese syndrome differentiation. However, the comparative effectiveness among these six formulas has not been investigated in published randomised controlled trials. We plan to summarise the direct and indirect evidence for these six formulas combined with pharmacotherapy to determine the relative merits options for the management of AECOPD. Methods and analysis: We will perform the comprehensive search for the randomised controlled trials to evaluate the effectiveness of six Chinese herb formulas recommended in Chinese medicine clinical guideline or textbook. The combination of pharmacotherapy includes bronchodilators, antibiotics and corticosteroids that are routinely prescribed for AECOPD. The primary outcome will be lung function, arterial blood gases and length of hospital stay. The data screening and extraction will be conducted by two different reviewers. The quality of RCT will be assessed according to the Cochrane handbook risk of bias tool. The Bayes of network meta-analysis (NMA) will be conducted with WinBUGS to compare the effectiveness of six formulas. We will also use the surface under the cumulative ranking curve (SUCRA) to obtain the comprehensive rank for these treatments. Ethics and dissemination: This review does not require ethics approval and the results of NMA will be submitted to a peer-review journal. Trial registration number: PROSPERO (CRD42016052699).